PEMANFAATAN LIMBAH PLASTIK LDPE PADA CAMPURAN ASPAL BETON MENGGUNAKAN ASPAL MODIFIKASI PG 70 - Syahrizal Abdullah Razak; Hartatik, Nurani; Hariani, Hariani; Punarta, I Gede Agus (Jurnal Teknik Sipil dan Arsitektur, 2025)
Plastic waste management in Indonesia is an important issue in realizing sustainable waste management. Based on data from 2021, Indonesia produces around 25.95 million tons of plastic waste, equivalent to 15.96% of the total national waste production. Plastic waste occupies the second position after organic waste in the composition of waste in Indonesia. One of the efforts to utilize plastic waste is to integrate it as a binder in asphalt concrete mixtures. The asphalt concrete layer is a pavement layer that directly receives vehicle loads, is designed to withstand changes in temperature, shear forces, vertical pressure, and functions as a waterproof layer. In this study, Low-Density Polyethylene (LDPE) plastic waste was used after washing, shredding, and drying. LDPE was then mixed with asphalt through wet mixing method. This research aims to evaluate the effect of LDPE plastic waste addition on the quality of modified asphalt mixture, especially on the aspects of stability, flexibility, and crack resistance. Tests were conducted using the Marshall method to obtain parameters such as stability, flow, voids in the mixture (VIM), voids between aggregate grains (VMA), and voids filled with asphalt (VFA). The test results showed that the penetration value of PG 70 modified asphalt tended to decrease as the LDPE plastic waste content increased, from 55 cm at 0% to 44.13 cm at 6%, indicating an increase in asphalt hardness. The highest flash point was reached at 6% LDPE content of 375.67 °C, while the lowest flash point was 367 °C at 0% content, indicating increased thermal safety. In addition, the highest softening point was recorded at 6% LDPE content of 61.8 °C, while the lowest softening point was 52.9 °C at 0% content. This shows that the addition of LDPE increases the resistance of asphalt to high temperatures and still meets the technical standards set by the 2018 Bina Marga General Specifications. These findings indicate that the utilization of LDPE plastic waste in asphalt mixtures can be an innovative solution in reducing the volume of plastic waste while improving pavement quality. Keyword: LDPE Plastic Waste, Modified Asphalt, Asphalt Concrete, Marshall Test.